Cancer chemoprevention with PV-1, a novel Prunella vulgaris-containing herbal mixture that remodels the tumor immune microenvironment in mice - Zhang, Qi; Chen, Xu; Palen, Katie; Johnson, Bryon; Bui, Dinh; Xiong, Donghai; Pan, Jing; Hu, Ming; Wang, Yian; You, Ming (Frontiers in Immunology, 2023)
The herb Prunella vulgaris has shown significant immune-stimulatory and anti-inflammatory effects in mouse models. Here, the effects of a novel Prunella vulgaris-containing herbal mixture, PV-1, were examined in several mouse models for cancer, including chemically induced models of lung and oral cancers as well as syngraft models for lung cancer and melanoma. PV-1, consisting of extracts from Prunella vulgaris, Polygonum bistorta, Sonchus brachyotus and Dictamnus dasycarpus, exhibited no toxicity in a dose escalation study in A/J mice. PV-1 significantly inhibited mouse lung tumor development induced by the lung carcinogens vinyl carbamate and benzo[a]pyrene. PV-1 also hindered the induction of oral squamous cell carcinomas in C57BL/6 mice caused by 4-nitroquinoline-1-oxide. Flow cytometry analysis showed that PV-1 increased the numbers of CD8+ tumor-infiltrating lymphocytes (TILs) and increased the production of granzyme B, TNF-α, and IFN-γ by CD8+ TILs. PV-1 also suppressed granulocytic myeloid-derived suppressor cell numbers (g-MDSCs) and improved the anti‐cancer activity of anti-PD‐1 immunotherapy. These results indicate that PV-1 remodels the tumor immune microenvironment by selectively inhibiting g‐MDSCs and increasing CD8+ TILs within tumors, resulting in decreased immune suppression and enhanced cancer chemopreventive efficacy.